(3GdeYhfIs - (3GHf GdgGFe, CMeO Hf eMeO Hf YeGO GdOjf, J(B815(3g`s
(3ChdgG (B:s
(3GdMeO ddg YOO fYeGFgCeG HYO agPg QSGdI aj Yde GdMSGHhSejJgG HGdeYhfIGdebOeI ajgG eSGFd GdChdi aj JYQja Yde GdMSGHs
(3BNQgG (B:s
(3GdKGfjI jHb GdMQa GdKGfj Ke GdLedI GdKGdKI jHb GdKGdK hgcPG Edi Cf jWQM GdLedI GdCNjQI ajHbi GdMQa GdCNjQ aQcH GdMQha jcf GdGSe GdeVeQs
(3efbhdI ef fSNI GdeDda GdeDQNI SfI (B791(3g`s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: 1 / 226s
(3eYLe GdeDdajf(B: 1 / 284s
(3cTa GdXfhf(B: 2 / 1743s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdQjGVjGJs